Effect of integrated plant nutrient management system in quality of mandarin orange (Citrus reticulata Blanco) - Bishnu Prasad Kandel; Lal Bahadur Chhetri (Jurnal Agercolere, 2019)
Nepal is a major producer among top twenty producing country of mandarin orange in the world. The productivity of the mandarin orange is very low as compared to other developed countries. Nutrient management is the serious problem in most of the orchard along the country. The experiment was conducted in Baglung district of Gandaki Province, Nepal in 2017 to study the effect of Integrated Plant Nutrient Management System (IPNMs) in quality parameters of mandarin orange. Seven group of treatment were assigned for experiment. All treatments were replicated three times in randomized complete block design. The fruits of T4 (Integrated nutrient) have greater fruit diameter: 5.26 cm, weight: 83.32 g total soluble solid: 14.53 brix % and lower titratable acidity: 0.846%. Fruits of T7 have more peel percentage (26.07%). These all findings indicate, integrated plant nutrient management system governs the quality of fresh mandarin orange.